2012
DOI: 10.2176/nmc.52.636
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Subdural Hematoma Associated With Traumatic Intracranial Interhemispheric Subdural Hematoma

Abstract: A 78-year-old female fell and hit the back of her head on the floor. Head computed tomography (CT) showed right acute interhemispheric subdural hematoma (ISDH). Her left hemiparesis worsened, so partial removal of ISDH was performed. The hemiparesis was improved, but leg monoparesis persisted. Lumbar magnetic resonance imaging showed spinal subdural hematoma (SSDH) at the S1-2 level. Nerve conduction velocity measurements at the knee joint to lower limb showed disappearance of the left peroneal nerve conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…9,11,18,38,44 Interestingly, among the 17 earlier trauma patients, 7 (41%) also had a bleeding tendency, 1 presented with blood dyscrasia, and 6 were on drug therapy that can affect bleeding. 7,17,20,29,30,40,41 The patient in our Case 1 also had a history of myelo dysplastic syndrome and hemorrhagic diathesis. Russell and Benoit 33 reviewed 58 cases involving patients with spinal SDH and found that in 16%, SDH occurred after anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…9,11,18,38,44 Interestingly, among the 17 earlier trauma patients, 7 (41%) also had a bleeding tendency, 1 presented with blood dyscrasia, and 6 were on drug therapy that can affect bleeding. 7,17,20,29,30,40,41 The patient in our Case 1 also had a history of myelo dysplastic syndrome and hemorrhagic diathesis. Russell and Benoit 33 reviewed 58 cases involving patients with spinal SDH and found that in 16%, SDH occurred after anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 79%
“…The etiology remained unclear in the 35 previously reported cases (Table 1). Of these cases, 3 involved patients who had undergone ventricu loperitoneal (VP) shunt placement, 31,37,42 3 cases were postcraniotomy, 26,36,43 17 were posttrauma, 1,4,5,7,8,13,17,20,21,24,29,30,34,35,[39][40][41] and in 12 cases the SDH arose spontaneous ly. [9][10][11]16,18,22,25,28,30,38,44,45 Leakage of intracranial SDH fluid into the spinal subdural space may be involved in patients who manifest spinal SDH after VP shunt placement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations